INTERACTIVE CLOTHING DESIGN LESSONS BASED ON CULTURAL HERITAGE - Rajabova Nilufar Shuhratovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores interactive clothing design lessons that integrate cultural heritage elements. It examines how traditional motifs, patterns, and colors can be incorporated into modern fashion education to enhance students’ creativity, technical skills, and cultural awareness. The study highlights pedagogical strategies for using interactive methods, including project-based assignments, digital tools, and collaborative activities, to make heritage-based design learning engaging and effective.